2021
DOI: 10.1093/cid/ciab255
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Localization of Blood-Borne Loa loa Microfilariae in the Skin Depends on Microfilarial Density in the Blood: Implications for Onchocerciasis Diagnosis in Coendemic Areas

Abstract: Background The diagnostic gold standard for onchocerciasis relies on identification and enumeration of (skin-dwelling) Onchocerca volvulus microfilariae (mf) using the skin snip technique (SST). In a recent study, blood-borne Loa loa mf were found by SST in individuals heavily infected with L. loa, and microscopically misidentified as O. volvulus due to their superficially similar morphology. This study investigates the relationship between L. loa microfilarial density (Loa MFD) and the proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Indeed, recent studies found that high L . loa microfilaremia can lead to false-positive results for the RDTs used for LF [ 124 126 ] and skin snips for onchocerciasis diagnosis [ 127 , 128 ]. Current mapping of onchocerciasis and LF in central Africa should be interpreted with caution in L .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent studies found that high L . loa microfilaremia can lead to false-positive results for the RDTs used for LF [ 124 126 ] and skin snips for onchocerciasis diagnosis [ 127 , 128 ]. Current mapping of onchocerciasis and LF in central Africa should be interpreted with caution in L .…”
Section: Discussionmentioning
confidence: 99%
“…While the diagnostic performance of some RDTs is good [122,123], improvements are still needed. Indeed, recent studies found that high L. loa microfilaremia can lead to false-positive results for the RDTs used for LF [124][125][126] and skin snips for onchocerciasis diagnosis [127,128]. Current mapping of onchocerciasis and LF in central Africa should be interpreted with caution in L. loa coendemic areas, and further mapping should jointly assess L. loa microfilarial density during these surveys.…”
Section: Discussionmentioning
confidence: 99%